Prevalence and Correlates of Overweight/Obesity, Physical Activity, And Sedentary Behaviour Among School-aged Children in Kenya - Muthuri, Stella K. (Université d'Ottawa / University of Ottawa, 2014)
In recent years, physical activity and fitness transitions, described as declines in physical activity and aerobic fitness, coupled with increased sedentary behaviour, have been observed among school-aged children. Consequently, the prevalence of childhood overweight/obesity has also increased considerably. While there is a wealth of evidence supporting such behavioural transitions in higher income countries, there exists a paucity of data on the situation in lower income countries, such as those in Sub-Saharan Africa (SSA). The premise of this thesis was to investigate the robustness of these relationships in other global regions. The first objective was to investigate the evidence for an overweight/obesity, physical activity, and fitness transition among SSA’s school-aged children. Systematic review methodology was used to examine temporal trends and correlates of overweight/obesity, physical activity, fitness, and sedentary behaviour in apparently healthy or population based samples of children (5 - 17 years). The second objective of this thesis was to determine the prevalence and correlates of overweight/obesity and physical activity among Kenyan children aged 9 to 11 years, having contextualised Kenya within the broader situation in SSA. Further, the relationships between self-reported and directly assessed measures of physical activity and sedentary time by weight status in Kenyan children were investigated. The third objective was to examine moderate-to-vigorous physical activity (MVPA) patterns accrued by time of day among Kenyan children using the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE)-Kenya data. Activity patterns in the Kenyan setting were then compared to similar ISCOLE-Canada data from Canadian children, revealing differences and similarities in the accumulation of MVPA, light physical activity, and sedentary time. Systematic review data syntheses revealed a trend towards increasing proportions of overweight/obesity among Sub-Saharan Africa’s school-aged children. Further, urbanization and higher socioeconomic status (SES) were associated with decreased physical activity and aerobic fitness, and increased sedentary behaviours and body composition measures. ISCOLE-Kenya data analyses found a prevalence of childhood overweight/obesity of 20.8% in Nairobi, with few children meeting global physical activity guidelines (12.6%). Mean daily sedentary time was 398 minutes, time spent in light physical activity was 463 minutes, and time spent in MVPA was 36 minutes. Higher SES and parental education attainment were associated with a higher likelihood of children being overweight/obese and a lower likelihood of children meeting the physical activity recommendations. Data analyses also revealed considerable discrepancies in both self-report and direct measures of physical activity by weight status, and weak to moderate correlations between self-report and direct measures of physical activity. Under/healthy weight children had significantly higher directly measured mean daily minutes of MVPA compared to overweight/obese children (39 verses 20 minutes); had lower mean weekend-day minutes of sedentary time (346 verses 365 minutes); and had a higher proportion who met physical activity guidelines (15.5% versus 2.6%). Lastly, while MVPA patterns among urban Kenyan children were largely similar to those of urban Canadian children with regard to relationships by sex, BMI category, and weekday/weekend days; in the Kenyan sample, much unlike many higher income countries, lower SES was associated with higher MVPA.
Keywords: Overweight/obesity; Physical Activity; Sedentary Behaviours; Physical Fitness; Behavioural Transitions; Accelerometry; Self-Report; Child; Sub-Saharan Africa; Kenya; Canada